Seven Habits of Great Indonesian Children in Early Childhood Education Contexts: A Qualitative Study - Ismah, Teta Nurul (Qualitative Research in Early Childhood Education, 2026)
Early childhood education plays a crucial role in shaping children’s character, habits, and lifelong learning dispositions. In Indonesia, national educational values emphasize the development of holistic individuals who are spiritually grounded, socially responsible, independent, and resilient. However, limited empirical research has explored how these values are manifested in children’s daily practices within early childhood education settings. This study aims to explore and describe the Seven Habits of Great Indonesian Children as reflected in everyday learning activities. A qualitative descriptive approach was employed, involving classroom observations, semi-structured interviews with teachers, and document analysis of educational programs. The study was conducted in selected early childhood education centers that actively implement character-based learning. Data were analyzed using thematic analysis to identify patterns and meanings related to children’s habitual behaviors. The findings reveal seven interconnected habits: spiritual awareness, discipline and responsibility, independence, cooperation, respect and empathy, curiosity and love of learning, and healthy living practices. These habits are embedded in daily routines, teacher modeling, and culturally grounded learning activities. The results highlight that habit formation occurs through consistent practice, social interaction, and supportive learning environments. This study contributes to the literature by providing a culturally contextualized understanding of character education in early childhood. The findings offer practical implications for educators and policymakers in strengthening habit-based learning approaches. Integrating these habits into early childhood education is essential for fostering well-rounded children who are prepared for future challenges.